Critical Discourse Analysis In The Lyrics of A Song Entitled”Polisi Dan Bajingan By Iwan Fals. - Fathoni, M.fathoni; Ibnu Akbar; Suhaeli Robbi Awaludin; Gustin Rainaldi; Slamet Riadi Jaelani (Kirana Publisher (KNPub), 2023)
In analyzing a song lyrics means aiming to understand and express the overall meaning of the lyrics of a song as a whole, because a song is not only for entertainment, but also expressing feeling, message, and character building. this study using qualitative methods about the object of research .The researcher emloys the Critical Discourse Analysis (CDA) as the framework of the research. The type of CDA that has been used is based on the Van Dijk theory. The theory is formulated in three stages, which were text , socio cognition and context. The stage of text itself is divided into three, namely macrostructure,superstructure, and macrostructure. The step of research is begun by collecting all song lyrics by Iwan Fals from his song entitled “ Polisi dan Bajingan”. Further, the next step is choosing the song lyrics needed for research.but, in this research the writer find one level to be analyzed, that is macrostructure. One of figures song writer and singer who has composed and published some inspirited songs is Iwan Fals. He is a singer, musician, songwriter, and critic. His musical style is pop, rock, country, and folk pop and the lyrics he creates tell a lot about the dark times in the era of 1970 to 1980 in the political field. In his career he has created approximately 31 albums. Iwan Fals is included in the list of the immortals: 25 greatest Indonesian artists of all time by Rolling Stone Indonesia magazine. In his song, he photographed the social atmosphere of Indonesian life in the late 1970s until now the life of the world in general and life itself. For example the song